Anterior Thalamic High Frequency Band Activity Is Coupled with Theta Oscillations at Rest - Sweeney-Reed, Catherine M.; Zaehle, Tino; Voges, Jürgen; Schmitt, Friedhelm C.; Buentjen, Lars; Borchardt, Viola; Walter, Martin; Hinrichs, Hermann; Heinze, Hans-Jochen; Rugg, Michael D.; Knight, Robert T. (Frontiers in Human Neuroscience, 2017)
Cross-frequency coupling between slow and fast brain rhythms, in the form of phase-amplitude coupling (PAC), is proposed to enable the coordination of neural oscillatory activity required for cognitive processing. PAC has been identified in the neocortex and mesial temporal regions, varying according to the cognitive task being performed and also at rest. PAC has also been observed in the anterior thalamic nucleus (ATN) during memory processing. The thalamus is active during the resting state and has been proposed to be involved in switching between task-free cognitive states such as rest, in which attention is internally-focused, and externally-focused cognitive states, in which an individual engages with environmental stimuli. It is unknown whether PAC is an ongoing phenomenon during the resting state in the ATN, which is modulated during different cognitive states, or whether it only arises during the performance of specific tasks. We analyzed electrophysiological recordings of ATN activity during rest from 7 patients who received thalamic electrodes implanted for treatment of pharmacoresistant focal epilepsy. PAC was identified between theta (4-6 Hz) phase and high frequency band (80-150 Hz) amplitude during rest in all 7 patients, which diminished during engagement in tasks involving an external focus of attention. The findings are consistent with the proposal that theta-gamma coupling in the ATN is an ongoing phenomenon, which is modulated by task performance.